(untitled) (Journal of Health Sciences, 2022)
Introduction: Caring for patients with skin disorders is “more than skin deep”. Psoriasis is a systematic immune-mediated disease that generally does not affect survival, but certainly has major negative effects on patients. The previous research has reported that artificial restoration of a permeable barrier by occlusion results in regression of lesions in psoriasis.The aim of this research is to assess the efficacy of cling film dressing versus conventional treatment on palmoplantar psoriatic lesions among patients with psoriasis. Methods: The research design used in the study was a true experimental time series design. Block randomization was used to assign the study participants into either study or control group in a Psoriatic Out-Patient Department of tertiary care center at Southern part of India. As usual, the intervention group participants received the application of topical corticosteroid Eczivate MF with cling film wrap while the control group participants followed the conventional treatment (topical corticosteroid Eczivate MF without occlusive dressing). The modified psoriasis severity index (MPSI) score was used to measure the outcomes. Results: There was a high statistical significance difference on the severity of psoriatic disease level between the control and study groups (p ˂ 0.05). Conclusion: Steroidal cream application with occlusive dressing yielded better results than non-occlusive open treatment.